Marketing strategy - Cadogan, John W. (John William), 1968-; Sage eBooks (London : SAGE, 2009)
This reference collection presents an up-to-date picture of marketing strategy, one that reflects the historical origins and evolution of marketing strategy thought, and current and emerging themes within the marketing strategy literature.
Specialized.
Description based on print version record.
Includes bibliographical references.
Keywords: Marketing -- Management; Marketing -- Planning; Strategic planning; Electronic books